Rate of metal deformation in welded pipe sections during field tests - TSAPKO, Oleksii; BERDNYK, Oksana; PRUSOV, Dmytro (Ways to Improve Construction Efficiency, 2025)
It is known that tests on Menage Sharp and other samples with thicknesses that do not correspond to the thickness of pipe walls do not reflect the real picture of viscous-plastic and brittle failures, which does not allow the development of a methodology or model for predicting the final (failure-free) service life of gas pipelines with a long service life. At the same time, theoretical and laboratory studies do not always provide sufficient answers to questions directly related to ensuring the durability and accident-free operation of pipelines. It is likely that in the laboratory conditions of enterprises or scientific institutions, it is difficult to reproduce and take into account all the factors that characterize the growth and spread of destruction in a real gas pipeline. Therefore, laboratory research data must be verified and refined based on the results of pneumatic tests of long pipe sections, i.e., there is currently an urgent need to combine laboratory and field tests of gas pipeline network pipes. Such tests are not widespread, but they provide important information about the behavior and properties of metal under load and operating conditions that are closest to actual operating conditions. Field tests were conducted at a specially equipped test site on pipe sections intended for the construction of main gas pipelines, which made it possible to obtain the kinematic and dynamic parameters of the destruction of a model gas pipeline under working load and in conditions as close as possible to operational ones. Analysis of the results of field (full-scale) tests shows that from the moment of initiated failure in the central pipe, the speed of the main crack (on both sides of the initiator) increases and reaches its maximum at a distance of approximately 2-3 diameters from the notch. The change in speed along the length of the central pipe can be symmetrical relative to the notch made in the middle pipe or asymmetrical. This is due to the technique of conducting the experiment and the conditions of crack initiation, in particular, the displacement of the initiating notch relative to the middle of the pipe and the different properties of the pipe metal in the zone of local failure. A general pattern is the presence of a maximum velocity at the crack initiation stage. It should be noted that in order to conduct the experiment, the high fracture velocities achieved must be maintained when the crack tip enters the test sections. This condition is ensured by the appropriate selection of the viscosity of the central pipe metal.